Hairy Guys in Sheds: The Rough and Ready World of DIY Cigar Box Guitar Makers. (4th May 2018) - Atkinson, Paul
Abstract: The cigar box guitar has a long history in the USA, where it formed part of the culture of traditional blues music and became a popular DIY project. Despite the growth in popularity of the blues in the UK, the penchant for constructing cigar box guitars did not travel with it. This article explores the recent appearance of the instrument and the culture surrounding it in the UK as a particular form of cultural DIY activity combining individual design and production with collective performance, which has in some cases grown far beyond an amateur hobby into a professional business.